2021
DOI: 10.1038/s41598-021-94544-3
|View full text |Cite
|
Sign up to set email alerts
|

The value of GATA6 immunohistochemistry and computer-assisted diagnosis to predict clinical outcome in advanced pancreatic cancer

Abstract: Combination chemotherapy, either modified FOLFIRINOX (mFFX) or gemcitabine–nabpaclitaxel, are used in the treatment of most patients with advanced pancreatic ductal adenocarcinoma (PDAC), yet robust biomarkers of outcome are currently lacking to guide regimen selection. Here, we tested GATA6 immunohistochemistry (IHC) as a putative biomarker in advanced PDAC. GATA6 is a transcription factor in normal pancreas development. Two pathologists, blinded to clinical and molecular data, independently assessed GATA6 IH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…Another way to select patients that most benefit for neoadjuvant chemotherapy would be incorporating biomarkers selection, one example is the evaluation of GATA6 expression 8 , 17 . Tumors that express GATA6 , either detected by RNA sequencing or immunohistochemistry, are defined as classical subtype, and tend to have higher responses to FOLFIRINOX, in opposite of the basal-like subtype, which have low expression or do not express GATA6 , and have worse outcomes 8 , 17 , 18 . Finally, circulating cell-free tumor DNA could be a factor to stratify patients with better outcomes in future prospective trials, and possibly select patients that have benefit to neoadjuvant approaches 19 – 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Another way to select patients that most benefit for neoadjuvant chemotherapy would be incorporating biomarkers selection, one example is the evaluation of GATA6 expression 8 , 17 . Tumors that express GATA6 , either detected by RNA sequencing or immunohistochemistry, are defined as classical subtype, and tend to have higher responses to FOLFIRINOX, in opposite of the basal-like subtype, which have low expression or do not express GATA6 , and have worse outcomes 8 , 17 , 18 . Finally, circulating cell-free tumor DNA could be a factor to stratify patients with better outcomes in future prospective trials, and possibly select patients that have benefit to neoadjuvant approaches 19 – 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Classical PDAC showed that higher GATA6 mRNA expression is associated with a better prognosis ( 35 , 36 ). Additionally, low GATA6 expression is associated with shorter OS ( 37 ). Our data showed that GATA6 mutations were associated with a shorter PFS.…”
Section: Discussionmentioning
confidence: 99%
“…The limitation of computer image analysis is the inability to distinguish between different cell types such as normal cells and tumor cells 17 . Consequently, representative regions of lymphoma must be chosen carefully by pathologists.…”
Section: Discussionmentioning
confidence: 99%